Predictive model for growth of Clostridium botulinum from spores during cooling of cooked ground chicken. (November 2021) - Juneja, Vijay K.; Xu, Xinran; Osoria, Marangeli; Glass, Kathleen A.; Schill, Kristin M.; Golden, Max C.; Schaffner, Donald W.; Dev Kumar, Govindaraj; Dunn, Laurel; Jadeja, Ravi; Shrestha, Subash; Mishra, Abhinav
Graphical abstract: Highlights: Growth kinetics of Clostridium botulinum in chicken was investigated. Baranyi growth model was used to estimate the growth in chicken. A dynamic model to estimate growth was developed. The model will assist the food industry to evaluate risk of Clostridium botulinum in chicken. Abstract: Cooking temperature of poultry meat is typically inadequate to inactivate the heat resistant spores of Clostridium botulinum . The purpose of this study is to develop a predictive model for C. botulinum during cooling of cooked ground chicken. Cooked chicken was inoculated with a cocktail of five strains of proteolytic C. botulinum type A and five strains of proteolytic C. botulinum type B to yield a final spore concentration of approximately 2 log CFU/g. The growth of C. botulinum was determined at constant temperatures from 10 to 46 °C. Dynamic temperature experiments were performed with continued cooling from 54.4 to 4.4 °C or 7.2 °C in mono- or bi-phasic cooling profiles, respectively. The Baranyi primary model was used to fit growth data and the modified Ratkowsky secondary model was used to fit growth rates with respect to temperature. The primary models fitted the growth data well (R 2 values ranging from 0.811 to 0.988). The R 2 and root mean square error (RMSE) of the modified Ratkowsky secondary model were 0.95 and 0.06, respectively. Out of 11 prediction error values calculated in this study, ten were within the limit of acceptable prediction zone (−1.0 to 0.5), indicating a good fit of the model. The predictive model will assist institutional food service operations in determining the safety of cooked ground chicken subjected to different cooling periods.